Adequate or Inadequate? The Volume of Blood Submitted for Blood Culture at a Tertiary Children's Hospital. (October 2018) - Harewood, Freya C.; Curtis, Nigel; Daley, Andrew J.; Bryant, Penelope A.; Gwee, Amanda; Connell, Thomas G.
The volume of blood sampled for culture critically influences the results. This study aimed to determine (1) the volume of blood submitted for culture, (2) the proportion of blood cultures with adequate volume, (3) whether measured improvement from a previous educational intervention had been sustained, and (4) the impact of blood volume on culture result. The volume of blood submitted for cultures was determined over a 13-month period by weighing bottles before and after collection and before and after an educational intervention. The volume of blood submitted in 5127 culture bottles were measured. Fewer than 50% of all cultures were deemed adequate. A significant pathogen was isolated in 4.7% of blood cultures, and low-volume cultures were more likely to yield contaminant isolates (47/2422 [1.9%] vs 22/2705 [0.8%], P = .0005). Subsequently, the higher rate of contaminant isolates from low-volume cultures may affect selection and rationalization of antibiotic therapy.